PERLINDUNGAN HUKUM TERHADAP ALIH FUNGSI PERIZINAN DALAM TATA KELOLA PEMBANGUNAN LINGKUNGAN LAHAN PERTANIAN MENJADI LAHAN PEMUKIMAN DI KABUPATEN SIDOARJO - Erdianto, Tarkit (Jurnal Hukum Magnum Opus, 2021)
AbstractLand availability is an important factor to ensure the availability of food and a place to carry out other economic activities outside of agriculture. The occurrence of population growth and the development of economic activity affects the demand side for land, whose area is fixed. The problem of changing the function of agricultural land to non-agricultural is currently increasing. There is an increasing need for land for development, while the relative availability of land has led to competition in land use. Sidoarjo Regency has also changed the function of agricultural land, especially rice fields. From 2009 to 2018, the rice field area has decreased by 5,750 hectares. Sidoarjo Regency is one of the areas that experienced the highest shrinkage in East Java Province. This is the focus of serious attention for the Sidorajo Regency government to ensure the availability of agricultural land by protecting the environment and environmental development governance which has changed the paradigm of agricultural land into residential land. In the end, between the environment and the settlement, there must be a natural balance in maintaining a sustainable environment and based on the principle of an environment of sustainable development. This type of research used in this research is normative legal research. By using primary and secondary legal materials, along with tertiary legal materials as supporting materials. Based on research results and findings, agricultural land in Sidoarjo Regency is getting narrower and more rigid. This is because there is a form of development for settlements by changing the function of agricultural land and buying and selling agricultural land for housing and housing investment. Approximately 52,000 ha of chopped agricultural land were converted into housing and housing investment. At the level of environmental development on agricultural land in Sidoarjo district, it can be said that it violates the management of the agricultural environment, where it should be for water absorption and agricultural land ecosystems, then misused into residential and housing land for investment and housing. In the end, there must be legal protection for the environment of agricultural land for the people of Sidoarjo and the application of administrative sanctions, as well as criminal sanctions if some investors or developers, as in the Regional Regulation (Perda) Number 6 of 2009 concerning the Regional Spatial Plan (RTRW) of Sidoarjo Regency.Keywords: development governance licensing function transfer; legal protectionAbstrakKetersediaan tanah merupakan faktor penting untuk menjamin tersedianya pangan dan tempat untuk melangsungkan kegiatan ekonomi lain di luar pertanian. Terjadinya pertambahan penduduk dan perkembangan kegiatan ekonomi mempengaruhi sisi permintaan tanah yang luasnya bersifat tetap. Permasalahan alih fungsi lahan pertanian menjadi non pertanian saat ini terus mengalami peningkatan. Adanya peningkatan kebutuhan lahan untuk pembangunan, sementara ketersediaan lahan relatif tetap menyebabkan persaingan dalam pemanfaatan lahan. Kabupaten Sidoarjo juga mengalami alih fungsi lahan pertanian terutama sawah. Dari tahun 2009- 2018 luas lahan sawah mengalami penyususutan sebesar 5.750 hektar. Kabupaten Sidoarjo merupakan salah satu daerah yang mengalami penyusutan tertinggi di Provinsi Jawa Timur. Hal inilah menjadi fokus perhatian yang serius bagi pemerintah Kabupaten Sidorajo untuk menjamin ketersedian lahan pertanian dengan cara menjaga lingkungan hidup dan tata kelola pembangunan lingkungan yang mengalami perubahan paradigma lahan pertanian menjadi lahan pemukiman. Pada akhirnya antara lingkungan hidup dan pemukiman itu harus ada keseimbangan alam dalam menjaga lingkungan hidup yang berkelanjutan dan berprinsip pada environment of sustainable development. Jenis penelitian yang digunakan dalam penelitian ini ialah penelitian hukum normatif. Dengan menggunakan bahan hukum primer dan sekunder, beserta bahan hukum tersier sebagai bahan pendukung. Berdasarkan hasil penelitian dan temuan bahwa lahan pertanian di Kabupaten Sidoarjo sudah semakin sempit dan rigid. Hal ini dikarenakan ada suatu bentuk pembangunan untuk pemukiman dengan cara alih fungsi lahan pertanian serta jual beli lahan pertanian untuk perumahan dan investasi perumahan. Kurang lebih 52.000 ha lahan pertanian yang terpangkas berubah alih fungsi menjadi pemukiman dan investasi perumahan. Pada tataran pembangunan lingkungan hidup terhadap lahan pertanian di kabupaten Sidoarjo sudah dapat dikatakan menyalahi tata kelola lingkungan pertanian, di mana seharusnya untuk resapan air dan ekosistem lahan pertanian, kemudian disalahgunakan menjadi lahan pemukiman dan perumahan untuk investasi maupun tempat tinggal. Pada akhirnya, harus ada perlindungan hukum lingkungan lahan pertanian untuk masyarakat Sidoarjo dan penerapan sanksi administrasi, serta sanksi pidana apabila beberapa investor maupun pengembang, sebagaimana dalam aturan Peraturan Daerah (Perda) Nomor 6 tahun 2009 tentang Rencana Tata Ruang Wilayah (RTRW) Kabupaten Sidoarjo.